Reused From Banquet to Grave: Gold Glass, a “Popular” Medium in Late Antiquity? - Croci, Chiara (Eikón / Imago, 2022)
Gold glass bottoms generally found in Roman catacombs, are some of late antiquity’s most enigmatic objects. Originally conceived as vessels, once they were broken, their bases were reemployed to be embedded in the mortar sealing of the slabs of certain loculi. Drawing on the different hypotheses on the origins of the bowls or glasses these bottoms were obtained from, and reflecting on the reasons for and ways of using these glass bottoms to decorate loculi, this paper aims to reassess the position of gold glass in the culture of late antiquity by questioning its pertinence or link to "popular" culture.